(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Shree Vanalakshmi GaneshpuraMahila Sewa VrukshUtpadakSahkari Mandli Ltd, created with the intention to provide employment to marginal womeninGaneshpura village, situated in the Mehsana district of Gujarat, is now an Eco-Tourism center too. It started with 41 women, who transformedbarren 10-acre land into an irrigated plot growing various fruits, vegetables, various types of ayurvedic plants, trees, etc. The entire model is unique in nature supporting the self-reliance of these SEWA sisters. The visitors enjoy its beauty, nature, Gujarati food, culture, organic fruits and vegetables,and the peace of this place.